Malignant mesothelioma of the pleura – progress in diagnostics and treatment - Drozdowska, Adrianna (Contemporary Oncology/Współczesna Onkologia, 2003)
Malignant mesothelioma of the pleura is a rare neoplasm with a poor prognosis. This tumor constitutes a difficult diagnostic and therapeutical problem. Diagnosis is often delayed due to nonspecific clinical symptoms, a variety of radiological images and a similarity to other neoplasms particularly adenocarcinoma in microscopical evaluation. The mainstay of diagnosis is histological and immunohistochemical analysis of microscopic samples obtained during thoracoscopy. However, in spite of the development of highly specific and sensitive antibodies, differentiation between mesothelioma and adenocarcinoma still remains difficult. Despite progress in therapy, the outcome in pleural mesothelioma is still unsatisfactory. Radical treatment including pleuropneumonectomy followed by chemotherapy and radiotherapy is possible in only a small group of patients with early diagnosis. Recently introduced new chemotherapeutic agents have been demonstrated to produce relatively high response rates (up to 30%). The most active combination so far (pemetrexed and cisplatin) improves the overall survival, pulmonary function and quality of life. Radiotherapy plays an important role in the palliative treatment of the chest pain and is used as an adjuvant to surgery. Palliative therapy including chemical pleurodesis, decortication, parietal pleurectomy and pleuroperitoneal shunting, are relatively efficient in the relieving of effusion-caused dyspnea. Novel treatment approaches (photodynamic therapy, immunotherapy and gene therapy) in the management of pleural mesothelioma are currently a matter of clinical investigation.